Symbolism And Local Wisdom In The Traditional Ceremonies Of The Community Of Jombang, East Java - Nur Hanifatul Zakiyah (Eduvest - Journal of Universal Studies, 2025)
This study examines the symbolism and local wisdom in the traditional ceremonies of the Jombang community, East Java, using Clifford Geertz's theory of cultural interpretation. The traditions studied include Grebeg Apem, Wiwit Kopi and Sedekah Bumi, Bersih Desa, Kenduren Wonosalam, and Kungkum Sinden. The research was conducted using a qualitative interpretive approach through library research and descriptive analysis of literary sources and cultural documentation. The results show that each tradition contains a system of symbols that represent religious, social, moral, and ecological values that exist in Javanese agrarian society. Grebeg Apem contains symbols of self-purification and social solidarity. Wiwit Kopi and Sedekah Bumi reflect gratitude for the harvest and respect for nature. Bersih Desa emphasizes collective awareness of social and spiritual balance. Kenduren Wonosalam displays an expression of togetherness and local identity through agricultural products. Meanwhile, Kungkum Sinden demonstrates the relationship between art, spirituality, and the preservation of ancestral heritage. Thus, all these traditions are a form of meaning system that integrates humans, culture and nature into a symbolic unity that confirms the identity of the Jombang people in the midst of modern social change.